Connect rural areas with digital innovations to unlock climate resilience for hundreds of millions of farmers - Koo, Jawoo; Gardeazábal Monsalve, Andrea (CGIAR System Organization, 2022)
Research shows that digital innovations can increase small-scale farmers’ incomes, boost the adoption of better practices, and increase resilience to climate shocks while reducing the gender gap and managing food system risks. However, these benefits are not universal. Over 600 million people and 40 percent of small farms are still not covered by mobile internet, especially in those countries most dependent on agricultural production. Across low- and middle-income countries, women are 7 percent less likely than men to own a mobile phone and 15 percent less likely to use mobile internet. A new CGIAR Research Initiative, Digital Innovation, has been launched to research pathways to bridge this digital divide, improve the quality of information systems, and strengthen local capacities to realize the potential of digital technologies.